PERANAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM PENGEMBANGAN STAF SMPN 18 SEMARANG - Risnawati, V Naniek (JURNAL STIE SEMARANG, 2009)
Supervision    is   meant   to   help   and   develop   teachers   to   be professional. With professional teachers, the final objective of supervision to   improve   student's    learning   could   be   achieved.   The   principal's responsibility  as a supervisor  is to help teachers  develop  their teaching capability. From the observation, it is found that a lot of principals have not conducted  their supervision  properly. Therefore,  it is worth studying  "the principal's role as a supervisor in the development of staff This study is specifically intended to examine the principal's  role as a supervisor  in the  development  of  staff  at  State  Junior  High  School  18 Semarang factors that affect his role (factors that support and those that inhibit), and the type of supervision  as expected  by teachers.  Based  on the findings, some recommendation  could be taken into consideration  by the   principal   as   a   supervisor    to   make    some    decision    on   the implementation of supervision in his school. This is a qualitative or naturalistic study. The data were collected  by the use of participant observation, interviews,  questionnaires,  and documents.  The validity  of the data was checked  by the  use of careful observation,  triangulation,  and member's  check. The data were analyzed by the  use  of  (a) data  reduction,        (b) data  display,  and  (c)  drawing concl usions/verification. Based on the analysis, the following conclusions  can be drawn. First, the supervision by Principal of State. Junior High School 18 Semarang   is delegated to the Vice Principal. Second, the Principal has  played hislher role as good supervisor. Third, some factors inhibit the implementation  of supervision.  One  of  them  is that  teachers  do  not  trust  their  supervisor making them less motivated in the implementation  of supervision.  Fourth, teachers  expect to have regular supervision  conducted  by a professional supervisor  to  guide  and  develop  them  in  their  teaching  and  learning process. If is recomended  that first,  principal  should  not fully  delegated  his supervision   responsibility;  second,  the  supervisor   should  be  selected based  on  his  capacity  for  supervision;   third,  there  should   be  good coordination  between the principal, the supervision  team, and teachers  in order to create conducive atmosphere and each of them could implement the supervision properly.